Sistem Informasi Pengukuran Efektivitas Produksi BerbasisWeb (Studi Kasus : PT. Beiersdorf Indonesia) - Diovianto Putra Rakhmadani; Soetam Rizky Wicaksono (Jurnal Rekayasa Sistem Industri, 2015)
The effectiveness of the production is a must knowledge in a manufacture company, because it is closelylinked to the success level of a company, if effectiveness reaching high level, it will lead to be successful interms of meeting production targets. It is also happened at PT Beiersdorf Indonesia which requires method tomeasure the effectiveness of production in their companies, particularly in Elastoplast production division.PT Beiersdorf Indonesia requires certain method IPC computerized checklist which the system can giveinformation related to the evaluation of the effectiveness of production. Based upon these problems, it is clearlystated that they need to use innovation in Effectiveness Level Measurement Information System Production.This information system is designed to help the all involved employees the process, documenting, and directlycontrols the activity of production. in this study, by creating the new system will help the company to conductan evaluation of the production process.